Policy innovation based on Policy Interventions for Community Groups with Poverty Problems Extreme Poverty in Banten Province - Sururi, Ahmad; Winangsih, Rahmi; Sukendar, Sukendar (Future Science, 2024)
The purpose of this research is to discuss intervention-based policy innovation in overcoming the problem of extreme poverty in Banten Province. The research method used is descriptive qualitative through interview data collection techniques and documentation studies, data analysis using Hierarchical Analysis Process (AHP), which is a method for solving a complex unstructured situation into several components in a hierarchical arrangement, by giving subjective values about the relative importance of each variable, and determining which variables have the highest priority to influence the outcome of the situation. The results showed that educative and participatory intervention policy innovation was the first priority alternative intervention strategy, then targeted nutrition policy intervention as an alternative intervention strategy, zero hunger strategy policy intervention as the third alternative intervention strategy, communication literacy policy intervention at the downstream of the fourth alternative intervention strategy policy and strong local leadership strengthening policy intervention as the fifth alternative intervention strategy.